2020
DOI: 10.1007/s13337-020-00611-0
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of SARS-CoV-2 in food safety and food hygiene: potential preventive measures, suggestions and nanotechnological approaches

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is easily transmitted from person to person, which has fueled the ongoing pandemic. Governments in different countries have taken drastic actions such as complete lockdown. However, little attention has been paid to food safety and its potential linkage with the coronavirus disease (COVID-19) pandemic. SARS-CoV-2 spread from staff to food products or food surfaces is conceivable. At least, instead of consuming unpackaged or uncovered foods, consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 50 publications
1
85
0
3
Order By: Relevance
“…Further evidence is needed to prove the connection between air pollution and COVID-19 infection. (2) Recent cases of COVID-19 suggested that the contaminated food with virus may cause transmission through the process of production, processing, transport, and selling ( Ceylan et al., 2020 ). Consequently, SARS-CoV-2 in food safety and hygiene should cause a concern, and prevention and regulatory strategies may be of high priority in the future.…”
Section: Advances and Concluding Remarksmentioning
confidence: 99%
“…Further evidence is needed to prove the connection between air pollution and COVID-19 infection. (2) Recent cases of COVID-19 suggested that the contaminated food with virus may cause transmission through the process of production, processing, transport, and selling ( Ceylan et al., 2020 ). Consequently, SARS-CoV-2 in food safety and hygiene should cause a concern, and prevention and regulatory strategies may be of high priority in the future.…”
Section: Advances and Concluding Remarksmentioning
confidence: 99%
“…This is mainly because the situation is rapidly evolving on COVID-19, particularly on viral contamination of foods and associated risks of SARS-CoV-2 transmission, which have only started attracting public and regulatory concerns after the recent events. Most of the evidence on SARS-CoV-2 detection on frozen foods appeared between July-August 2020, weeks or months later after the recent discussions on food-associated transmission of COVID-19 (Ceylan et al 2020;Eslami and Jalili 2020;Rizou et al 2020;Sharma et al 2020;Zuber and Brüssow 2020). Further, studies on the stability of SARS-CoV-2 in food environments only began to appear in early July 2020 (Fisher et al 2020;Harbourt et al 2020).…”
Section: Environmental Chemistry Lettersmentioning
confidence: 99%
“…In the early discussions on COVID-19, foodborne transmission was postulated as a potential risk factor (Sharma et al 2020 ), and precautionary measures were recommended for staff involved in preparing and distributing food (Eslami and Jalili 2020 ; Zuber and Brüssow 2020 ). In a brief discussion, Ceylan et al ( 2020 ) pointed out that foodborne diseases caused by viral infections are common, and viruses can contaminate food in three pathways, namely via contaminated water in which shellfish grows or used for fruit washing after harvest, poor hand hygiene practices, and the consumption of animal-based products containing zoonotic viruses. The authors further pointed out that foodborne transmission of SARS-CoV-2 needs to be studied, with several tasks suggested for future studies.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the recent FDA's statement, no scientific evidence exists to show a relationship between SARS-CoV-2 and food products. The administration of meat or other parts of infectious animals may cause zoonotic foodborne illnesses ( Ceylan, Meral, & Cetinkaya, 2020 ). In China, between early July to mid-August 2020, at least 9 occurrences of food contamination by SARS-CoV-2 reported on the packaging materials, storage environment, and surface of imported frozen raw foods ( Han, Zhang, He, & Jia, 2020 ).…”
Section: Introductionmentioning
confidence: 99%